A Hope Intervention Compared to Friendly Visitors as a Technique to Reduce Depression among Older Nursing Home Residents - Donna M. Wilson; Alexandra Marin; Param Bhardwaj; Bonnie Lichlyter; Amy Thurston; Deepthi Mohankumar (Nursing Research and Practice)
Depression is common among older persons. An experimental study was undertaken to test the impact of a four-week hope program on depressed nursing home residents. Residents aged 65 or older, who met the criteria for this pilot study and agreed to participate, were randomly assigned to (a) an intervention group, and provided with weekday hope interventions mainly involving positive messages and pictures or (b) a modified control group, and provided with a friendly weekday greeting. The structured hope intervention was not proven effective for reducing depression or raising hope. Instead, a significant reduction in depression among the control subjects was found, as well as a nonsignificant increase in their level of hope. Although these findings suggest friendly visitors may be a more efficacious nonpharmacological approach for reducing depression, further investigations are needed to confirm this and to explore the impact of other hope interventions.